Visual interpretation of children aged 3–8 toward non-dialogue animated films: A study on the impact on language development and imagination - Panjaitan, Angelia; Wibowo, Yudi (Imaji: Jurnal Seni dan Pendidikan Seni, 2025)
The phenomenon of speech delay in early childhood in Indonesia is increasingly prevalent, with estimates ranging from 5% to 8% among preschool-aged children, according to the Indonesian Pediatric Society (IDAI). One environmental factor under scrutiny is children's exposure to non-dialogue animated films, which are widely broadcast on Indonesian television, such as Larva, Shaun the Sheep, and Masha and the Bear. These shows rely heavily on visual storytelling and character expressions without spoken dialogue, raising concerns about their impact on children's language development. This study aims to analyze how children aged 3 to 8 interpret non-dialogue animated films through a visual semiotic lens. Roland Barthes’ semiotic theory is employed to examine the denotative and connotative meanings of visual signs, while Charles Sanders Peirce’s model is used to classify signs into icons, indices, and symbols. Using a qualitative descriptive method, this study analyzes visual texts and observes children's interpretive responses. The findings indicate that although children can grasp basic narrative messages through visual cues, the absence of verbal language input may hinder vocabulary growth and expressive language development, particularly in the absence of adult interaction. This study contributes to a deeper understanding of the relationship between non-verbal media consumption and the risk of speech delay in early childhood in Indonesia.